Skeletal muscle metastases in neuroblastoma share common progenitors with primary tumor and biologically resemble stage MS disease - Fong, Christina; Kushner, Brian H.; Di Giannatale, Angela; Gundem, Gunes; Li, Shanita; Roberts, Stephen S.; Basu, Ellen M.; Price, Anita; Cheung, Nai-Kong V.; Modak, Shakeel (Frontiers in Oncology, 2023)
Introduction While subcutaneous metastases are often observed with stage MS neuroblastoma, an entity that usually resolves spontaneously, skeletal muscle metastases (SMM) have been rarely described. The purpose of this retrospective study was to investigate the significance of SMM in neuroblastoma. Patients and methods Seventeen patients with neuroblastoma SMM were diagnosed at a median age of 4.3 (0.1-15.6) months. All had SMM at diagnosis and metastases at other sites. Fifteen (88%) had ≥ 2 SMM in disparate muscle groups. One, 14, and 2 patients had low, intermediate, and high-risk disease respectively. Fifteen tumors had favorable histology without MYCN amplification, and 2 were MYCN-amplified. Most SMM (80%; n=12/15 evaluated) were MIBG-avid. Results Only 1 patient (with MYCN-non-amplified neuroblastoma) had disease progression. All survive at median follow-up of 47.9 (16.9-318.9) months post-diagnosis. Biological markers (histology, chromosomal and genetic aberrations) were not prognostic. Whole genome sequencing of 3 matched primary and SMM lesions suggested that both primary and metastatic tumors arose from the same progenitor. SMM completely resolved in 10 patients by 12 months post-diagnosis. Of 4 patients managed with watchful observation alone without any cytotoxic therapy, 3 maintain complete remission with SMM resolving by 5, 13, and 21 months post-diagnosis respectively. Conclusions Children with neuroblastoma SMM have an excellent prognosis, with a clinical course suggestive of stage MS disease. Based on these results, the initial management of infants with non-MYCN-amplified NB with SMM could be watchful observation, which could eliminate or reduce exposure to genotoxic therapy.